2017
DOI: 10.7448/ias.20.01/21317
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in estimated glomerular filtration rate over time in South African HIV‐1‐infected patients receiving tenofovir: a retrospective cohort study

Abstract: Introduction: Tenofovir has been associated with decline in kidney function, but in patients with low baseline kidney function, improvements over time have been reported. Additionally, the magnitude and trajectory of estimated glomerular filtration rate (eGFR) changes may differ according to how eGFR is calculated. We described changes in eGFR over time, and the incidence of, and risk factors for, kidney toxicity, in a South African cohort.Methods: We included antiretroviral-naïve patients ≥16 years old who st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 42 publications
10
50
0
1
Order By: Relevance
“…This study found a low baseline prevalence rate of eGFR < 60 mL/min (1.9%), similar to that in a large published study from Zambia . Also similar to previous studies , this study showed lower baseline prevalence of renal dysfunction at baseline CD4 counts > 200 cells/μL and among younger individuals.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study found a low baseline prevalence rate of eGFR < 60 mL/min (1.9%), similar to that in a large published study from Zambia . Also similar to previous studies , this study showed lower baseline prevalence of renal dysfunction at baseline CD4 counts > 200 cells/μL and among younger individuals.…”
Section: Discussionsupporting
confidence: 90%
“…This is one of the first studies to evaluate the association between baseline CD4 count and renal dysfunction in the context of routine provision of ART regardless of CD4 count in a high‐burden programmatic setting. Probably as a result of this expanded ART access, the baseline median CD4 count in this study (328 cells/μL) was higher than that reported in previous studies from high‐burden settings . This study found a low baseline prevalence rate of eGFR < 60 mL/min (1.9%), similar to that in a large published study from Zambia .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Previous studies have shown that changes in renal function differ by the level of baseline renal function, with improvement in patients with baseline renal impairment but deterioration in patients with baseline normal renal function . Studies have also shown that cART could improve renal function among patients with advanced HIV stage at baseline .…”
Section: Introductionmentioning
confidence: 99%